Big data usage in telecommunications - Пономарёв, Артемий Александрович (Computer Tools in Education, 2015)
The article observes general questions of big data usage in practice in commercial activities of companies. The author makes an accent on the problems that can be solved in the telecommunications with the help of big data. He analyzes clients’ characteristics that help to judge about their potential churn rate. The author identifies clusters, for which the best prediction results were received.
Keywords: data; telecommnications; churn; support vector machines; neural networks